Studies on the Seeds and their Germination in Robina Pseudoacacia Linn. - Pathak, P S; Misra, C M; Roy, R Deb (Annals of Arid Zone, 2016)
Robinia pscudoacacia Linn. is a very important fodder cum fuel tree of higher altitudes. It produces the polymorphic seeds with hard seed coat which are difficult to germinate. Nine minutes scarification with concentrated sulphuric acid gives maximum germination. Pre-drying and pre-soaking improve germination to a certain degree. Effect of temperature, light and chemicals on seed germination is also studied.